Impact of sea Freight Rates to Railway Traffic: Case of Russian Railway - Daria Kochneva (Jurnal Ilmu Multidisiplin, 2025)
The purpose of the study is to assess the impact of sea freight rates on the import rail transportation market in Russia based on methods of correlation and regression analysis. To estimate the lag time of the influence of the price factor on the volume of transportation, the author’s “component shift” method was used. As a result, a regression model has been developed that makes it possible to predict the volume of railway transportation of imported products depending on the dynamics of sea freight and plan in advance measures to reserve railway capacity.